2011
DOI: 10.1097/aog.0b013e3182116bc8
|View full text |Cite
|
Sign up to set email alerts
|

Antimüllerian Hormone as a Predictor of Natural Fecundability in Women Aged 30–42 Years

Abstract: Objective To generate estimates of the association between markers of ovarian aging and natural fertility in a community sample at risk for ovarian aging. Methods Women aged 30–44 years with no history of infertility who had been trying to conceive for less than 3 months provided early-follicular phase serum and urine (N=100). Subsequently, these women kept a diary to record menstrual bleeding and intercourse and conducted standardized pregnancy testing for up to 6 months. Serum was analyzed for estradiol, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
110
5
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(126 citation statements)
references
References 30 publications
(25 reference statements)
4
110
5
6
Order By: Relevance
“…Thus, two different markers of ovarian reserve both seem to have an association with the qualitative aspect of the remaining oocyte pool. Also supporting this are the findings of a recent study on higher fecundability (the probability of a natural conception in a menstrual cycle) among women with high AMH levels compared with those with low AMH levels after adjustment for age (37). However, we need to await thorough genetic analyses for a definite conclusion on this probable relationship between ovarian reserve markers and oocyte quality.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, two different markers of ovarian reserve both seem to have an association with the qualitative aspect of the remaining oocyte pool. Also supporting this are the findings of a recent study on higher fecundability (the probability of a natural conception in a menstrual cycle) among women with high AMH levels compared with those with low AMH levels after adjustment for age (37). However, we need to await thorough genetic analyses for a definite conclusion on this probable relationship between ovarian reserve markers and oocyte quality.…”
Section: Discussionsupporting
confidence: 71%
“…Two recent prospective studies have shown conflicting results. There was a good correlation between AMH levels and natural conception in women 30-44 years of age during a 6-month observation period [42], but low AMH levels in a group of women in their twenties did not necessarily result in compromised fecundability [43]. These conflicting results may be due to the different ages of the study participants and to the small sizes of the study populations.…”
Section: General Population and Natural Conceptioncontrasting
confidence: 38%
“…This finding, shown also for AFC [18], suggests that AMH (and AFC) captures not only a quantity aspect but also, to some extent, a quality aspect of the remaining oocytes. In support of this interpretation, are data showing an association between fecundability and AMH levels in natural procreation [20].…”
supporting
confidence: 62%